Effectiveness of adjunct psychotherapy for cancer treatment: a review - Yoke Yong, Chen; Mahadir, Ahmad (Future Medicine Ltd, 2018)
Psychotherapies were offered to alleviate psychological and physical symptoms; however, most psycho- logical interventions were only delivered after cancer treatment. Newly diagnosed cancer patients ex- perienced psychological distress while waiting for treatments. This review paper focused on randomized control trial studies, aimed to investigate the effectiveness of psychological intervention among newly diagnosed cancer patients. Eight randomized control trial papers were found in recent 10 years period through electronic database. A moderate to large effect size was detected on the outcomes, ranging from 0.43 to 0.89. This indicated that psychological-based prehabilitation with standard care yielded better out- comes than standard care alone. Psychological-based prehabilitation provides evidence in its effectiveness to reduce psychological distress, functional impairment, recurrence of cancer, numbers of immune reac- tivity and sleeping quality; however, inconsistent with longer survival result among cancer patients. In conclusion, psychological-based prehabilitation before cancer treatment is necessary for better treatment outcome, and future research is needed to investigate more directly the outcome.